(untitled) - Anderson, Donald L. (California, 2015)
This book offers a comprehensive look at individual, team, and organizational change, covering classic and contemporary organization development techniques. Incorporating organization development ethics and values into each chapter, this book provides discussion of real-world application of these theoretical ideas to help students face today’s challenging environment of increased globalization, rapidly changing technologies, economic pressures, and changing expectations in the contemporary workforce.
Keywords: Organizational change,Thay đổi tổ chức; Management,Quản lý